STUDI KOMUNIKASI INTERPERSONAL DAN MANAJEMEN DIRI MAHASISWA PART TIME UTM DALAM MENERAPKAN WORK LIFE BALANCE - Panjaitan, Dearni Anjelina; Juliana, Yeni; Moh. Afdol; Shofia Zein; Febriansyah (JURNAL KOMUNITAS, 2025)
This study aims to understand how interpersonal communication strategies and self-management are carried out by Trunojoyo Madura University (UTM) students who work part-time in achieving work-life balance. This research is important considering that students are in the transition phase towards adulthood, where academic, social, and economic demands are increasingly complex. This research approach was qualitative with a case study type. The theory used was Abraham Maslow’s hierarchy of needs theory to explain work motivation and the interpersonal communication approach. Data were obtained through in-depth interviews and observations of five informants who are active UTM students working part-time for at least the last 3 months. Informants were selected using purposive sampling technique based on the relevance of the criteria, and assisted with snowball sampling if needed. The results showed that part-time students experience challenges in balancing academic and work activities. However, they usde adaptive interpersonal communication strategies and good self-management in dealing with work and study demands. This study emphasizes the importance of time management and social support in maintaining the work-life balance of working students.